1988
DOI: 10.1161/01.res.62.5.884
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nitroglycerin on aortic impedance, diameter, and pulse-wave velocity.

Abstract: The effects of an intravenous infusion of 1 |xg/kg/min nitroglycerin were studied on systemic arterial properties in nine acutely instrumented dogs. Aortic impedance and pulse-wave velocity were calculated from measured pressure and flow signals collected during random ventricular pacing. Central aortic diameter was simultaneously determined with ultrasonic dimension crystals. Mean blood pressure was maintained constant to avoid the confounding effects of passive, pressure-induced changes in vascular propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(51 citation statements)
references
References 21 publications
(19 reference statements)
4
47
0
Order By: Relevance
“…Yaginuma et al 25 and Fitchett et al 29 have measured ascending aortic impedance as well and have confirmed that this change in pressure was attributable to reduction of wave reflection from peripheral sites. This has recently been confirmed in dogs by Latson et al 30 Because the effect of nitroglycerin was seen without reduction in peripheral resistance, all investigators attributed this phenomenon to dilation of small conduit arteries. 25 -30 We have observed similar effects with nitroglycerin on the contour of the aortic 25 -31 and the carotid 27 arterial pressure wave, with the drug causing marked reduction in the amplitude of the late systolic pressure peak.…”
Section: Effects Of Vasodilator Agents On Arterial Wave Reflection Anmentioning
confidence: 74%
“…Yaginuma et al 25 and Fitchett et al 29 have measured ascending aortic impedance as well and have confirmed that this change in pressure was attributable to reduction of wave reflection from peripheral sites. This has recently been confirmed in dogs by Latson et al 30 Because the effect of nitroglycerin was seen without reduction in peripheral resistance, all investigators attributed this phenomenon to dilation of small conduit arteries. 25 -30 We have observed similar effects with nitroglycerin on the contour of the aortic 25 -31 and the carotid 27 arterial pressure wave, with the drug causing marked reduction in the amplitude of the late systolic pressure peak.…”
Section: Effects Of Vasodilator Agents On Arterial Wave Reflection Anmentioning
confidence: 74%
“…The increased AoRes index could result from increased aortic turbulence and shear stress generated by exaggerated flow following peripheral vasodilation. 39 However, the increased AoDist index remains difficult to explain. The relaxing effect of GTN is mediated through NO pathways and should affect muscular (such as the brachial artery) rather than elastic arteries (such as the aorta).…”
Section: Discussionmentioning
confidence: 99%
“…Estimates travel-time based on the phase-shift between two waveforms 31 . A line is fitted to the low frequency components of the quotient of the Fourier transforms of the two waveforms.…”
Section:  Fourier Analysis (Fa) Methodsmentioning
confidence: 99%